Seasonal limnological variation and nutrient load of the river system in Ibadan Metropolis, Nigeria (2008)
Ibadan is a highly populated city, characterized by environmental problems arising from improper disposal of solid and liquid wastes, poor wastes collection and handling. We therefore investigated the seasonal limnology and nutrient load of the river system in Ibadan metropolis, Nigeria during the dry season (October 2003-March 2004) and rainy season (August-September 2004). The results revealed that colour, Total suspended solid (TSS), total solids (TS) and total nitrogen were generally higher during the dry season. This suggests that the run-offs have only a diluting effect on these parameters. All the other physical parameters (pH, BOD, DO, COD, TDS, Total hardness) and Nutrient load based parameters (phosphate, sulphate, nitrate and nitrite) were generally higher during the rainy season. Also, in most of the sample points, BOD, TDS, TSS, colour and phosphate levels were relatively higher than the WHO standards for surface water during the two seasons. The poor water quality and nutrient loading observed in the study area has severe consequences on the in-dwelling aquatic flora and fauna. Proper treatment of effluent from industrial processes to acceptable levels, discouraging stagnation of domestic waste and sewage, availability of sewage treatment plants is necessary to curtail the health risk associated with the present level of pollution observed during this study.